Effective Response of Nonlinear Composite under External AC and DC Electric Field - Liu, Ye; Liang, Fang-Chu; Shen, Hong-Liang (Communications in theoretical physics, 2005)
A perturbation method is used to study effective response of nonlinear Kerr composites, which are subject to the constitutive relation of electric displacement and electric field, Dα=εαE＋xα｜E｜^2E. Under the external AG and DC electric field Eapp = Eα（1 ＋ sinωt）, the effective nonlinear responses and local potentials are induced by the cubic nonlinearity of Kerr materials at all harmonics. As an example in three dimensions, we have investigated this kind of nonlinear composites with spherical inclusions embedded in a host. At all harmonic frequencies, the potentials in inclusion and host regions are derived. Furthermore, the formulae of the effective linear and nonlinear responses are given in the dilute Iimit.